Assessing anthropogenic impact on the habitat of threatened rock cavy (Kerodon rupestris) through its alarm calls - Wesley N. Almeida; Kamila S. Barros; Sérgio L. G. Nogueira-Filho; Selene S. C. Nogueira (PLoS ONE, 2025)
Acoustic monitoring is emerging as a key tool in wildlife conservation, especially for species in inaccessible habitats like the rock cavy (Kerodon rupestris), an endangered species native to Brazil’s threatened Caatinga biome. Emotional stress from threatening situations affects breathing, heart rate, and vocal muscle tension, altering vocal acoustic parameters. This allows researchers to gauge the animal’s environmental perception through its vocalizations. We aimed to evaluate emotional disturbance indicators in free-range rock cavies’ vocalizations to suggest an acoustic index during threats. We compared calls from rock cavies in two areas with similar habitats but that differ in terms of anthropic impacts. Area 1 (A1) is near urban areas and disturbed by livestock and dogs, and Area 2 (A2) is farther from urban areas and free from human disturbance. Data on calls and behaviors were collected ad libitum in both areas. The alarm whistle call, making up 73.5% of total calls, was most common. Across 108 observation hours per area, 392 alarm whistle calls were recorded, with more calls in A1 than A2 (223 vs. 169; Chi-square = 29.44, DF = 1, P < 0.001). This resulted in a 32% higher hourly call rate in A1 (2.6 calls/h vs. 1.6 calls/h). Both male and female cavies in A1 had higher high-frequency (F1, 388 = 7.80, P = 0.005) and peak-frequency calls (F1, 388 = 21.32, P < 0.001). Given the similar landscape and resource availability in both areas, the differences in call emission rate and parameters are likely linked to emotional responses to human disturbances in A1. Thus, alarm whistle calls at an hourly rate of 2.6 calls/h or higher, with high-frequency and peak-frequency at or above 7222 Hz and 2603 Hz, can indicate anthropogenic disturbance in the Caatinga biome, aiding remote monitoring efforts.